Impact of dental caries on oral health related quality of life among preschool children: perceptions of parents - Mina Pakkhesal; Elham Riyahi; AliAkbar Naghavi Alhosseini; Parisa Amdjadi; Nasser Behnampour (BMC, 2021)
Abstract Background Childhood dental caries can affect the children's and their parents' oral health-related quality of life. The aim of the present study was to evaluate the impact of oral and dental health conditions on the oral health-related quality of life in preschool children and their parents. Methods In this descriptive-analytical cross-sectional study, samples were selected from children 3 to 6 years old enrolled in licensed kindergartens using "proportional allocation" sampling. Then, the parents of the children were asked to complete the Early Childhood Oral Health Impact Scale (ECOHIS). Results In this study, 350 children aged 3 to 6 years were evaluated with a mean age of 4.73 years. The mean dmft index (decayed, missed, and filled teeth) was 3.94 ± 4.17. The mean score of oral health-related quality of life was 11.88 ± 6.9, which 9.36 ± 5.02 belongs to the impact on children and 2.52 ± 3.20 to parents' impact. Conclusions The mean score of ECOHIS increased with the dmft index increase in children, indicating a significant relationship between the dmft and ECOHIS score. These outcomes can be used as proper resources to develop preventive policies and promote oral health in young children.